Exploring polyoxometalate speciation: the interplay of concentration, ionic strength, and buffer composition - Ždrnja, Maja; Gumerova, Nadiia I.; Rompel, Annette (Frontiers in Chemical Biology, 2024)
This study investigates the concentration-dependent speciation and stability of Keggin-type [P V W VI 12O40] 3-(PW12) and Wells-Dawson type [α-P V 2W VI 18O62] 6-(P2W18) polyoxotungstates across the pH range from 2 to 8 and buffer systems including acetic acid-sodium acetate, citric acid-sodium citrate, sodium phosphate, Tris-HCl, HEPES. Utilizing 31 P NMR spectroscopy for detailed analysis, we quantified the stability and hydrolysis patterns of PW12 and P2W18 in various buffer solutions at concentrations of 3, and 15 mM, and compared with previously published data for 10 mM solutions. Our research shows that higher concentrations of PW12 and P2W18 in solutions improve their stability in neutral to moderately alkaline environments (pH 7 and above), making them less prone to hydrolysis. This pronounced effect underscores the crucial role of concentration in optimizing the behavior of polyoxometalates under varying pH levels, revealing a strong link between concentration and stability across various buffers and highlighting how ionic strength, buffer composition, and pH crucially interact to influence POM stability. Research on how ionic strength affects the speciation of 3 mM solutions shows that the stability of P2W18 decreases as the pH approaches neutrality and as ionic strength increases, indicating heightened hydrolysis and reduced stability. For the inherently less stable PW12, the findings indicate a shift in hydrolysis pathwaysdifferent concentrations of the hydrolysis products, a change likely driven by the increased ionic strength. These findings emphatically underscore the critical importance of meticulously selecting the right buffer and concentration to fully unlock the potential of polyoxometalates such as PW12 and P2W18. Strategic choices are essential for leveraging these compounds as pivotal elements in groundbreaking applications, poised to revolutionize scientific and technological landscapes.